2018
DOI: 10.3390/admsci8040070
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Female-Led Startups. Do Women in Business Underperform?

Abstract: The spur of innovative startups has provided an unprecedented opportunity for female entrepreneurship. However, the mainstream literature on startups has elaborated a gender performance gap hypothesis. Considering the speed of technological, social, and cultural changes that have taken place in this millennium, we wonder if this gap can still be found today, with particular reference to new technology-based ventures. A financial analysis has been conducted on a sample of innovative Italian startups, and the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 53 publications
0
38
0
2
Order By: Relevance
“…However, the gender diversity situation in Russian startups is different from startups in developed markets. For example, only 15% of our Skolkovo sample (62 out of 416 startups) had at least one female owner and only 6% had woman CEO, which is significantly lower than the 42% share of female governance startups in the total population of innovative startups in Italy [20]. However, even in developed markets, the situation with gender diversity in startups is far from perfect.…”
Section: Entrepreneurs As Founders and Ownersmentioning
confidence: 75%
“…However, the gender diversity situation in Russian startups is different from startups in developed markets. For example, only 15% of our Skolkovo sample (62 out of 416 startups) had at least one female owner and only 6% had woman CEO, which is significantly lower than the 42% share of female governance startups in the total population of innovative startups in Italy [20]. However, even in developed markets, the situation with gender diversity in startups is far from perfect.…”
Section: Entrepreneurs As Founders and Ownersmentioning
confidence: 75%
“…Ewens and Townsend observed that when the investor in a startup with female owner(s) is a different woman, these startups are more successful, than if the investor was a man (Ewensa & Townsend 2020: 2). The reluctance of investors to finance startups run by women is puzzling in light of the data showing that these startups are characterized by a lower degree of debt and a slightly higher profitability (see Demartini 2018;Illuminate Ventures 2010). From the research of Loren Henderson et al (2015) follows that startups owned by men also receive significantly higher credit scores than do new firms owned by women in the opinion of banks (Henderson et al 2015: 477).…”
Section: Gender In the Context Of Technological Startupsmentioning
confidence: 99%
“…Reflecting this, Trentino is one of the few areas in Italy in which only a minority of start-ups is located in major "urban hubs": that is, 45.4% of start-ups located in the comune of Trento (Table 2.2). 6 Out of the 47 registered start-ups in Rovereto, a majority (29) share the address for their head office with one of these two centres. The share is even higher when formerly registered firms are considered (55 out of 87).…”
Section: Table 21 Distribution Of Start-ups and Population By Municmentioning
confidence: 99%